Tablet Gabapentin sebagai Analgesia Multimodal Perioperatif dalam Anestesi Umum - Widodo, Untung; Sarosa, Pandit; Gentong, Metia Gledis Gilang (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Multimodal analgesia is a combination of different drugs with different actions and targets in the nervoussystem, producing addictive effects or synergistic analgesia by reducing the side effects of single drug. The response of the humoral and neuronal complexes that occur due to surgery requires balanced perioperative pain management. Multimodal use can reduce the dose of each drug and reduce the incidence of side effects of drugs used for the treatment of perioperative pain, which can shorten hospitalization time, speed-up recovery and function of the body, and reduce health costs. Today, the American Society of Anesthesiologists Task Force on Acute Pain Management advocates the use of multimodal analgesia.